States and citizens accommodation, facilitation and resistance to globalization - Shefner, Jon, 1958- (Current perspectives in social theory ;, 2015)
Globalization has been subjected to a variety of analyses over the past thirty years, ranging from examinations of homogenizing cultural trends to the pressures of economic austerity and trade relations to the declining influence of states. This volume examines how states and citizens have been able to address globalization in different ways across the Global North and South. Authors examine the state as it forms policies in agro-production, contends with critical constituencies, and rebuilds capacity to act in the popular interest after forty years of neoliberal assault. Other contributors discuss citizen choices in the face of global markets as divergent as food, tourism, and pharmaceuticals, and examine the global reach of human rights efforts. This volume pushes forward theoretical understandings of how concrete institutions express agency even in the face of what seems like monolithic and inevitable structures of globalization. The actions taken by states and citizens further inform us about how globalization can be further shaped in the pursuit of social justice.